A study on drug smugglers: Malaysia as a transit / Nur 'Izzati Abdul Wahab…[et al.] - Abdul Wahab, Nur 'Izzati; Kamaruddin, Nur Nadia Hani; Nordin, Nazhirah; Ahmad, Nur Athirah (2011)
There is serious increase in the issues of drug smuggler for a decade. While the number of drug smugglers from foreign countries arrested in Malaysia has declined in the year of 2010, the problem is still a cause of concern. Strict enforcement of Malaysia drug laws seems ineffective in resolving this current issue. Thus, there are the needs to look into the causes regarding its effectiveness. Consequently, through analytical study, this research examines the efficiency of Malaysia laws in controlling drug trafficking and to highlight the implication of death penalty since there are increasing number of drug trafficking offences and to protect the person whom is victimized by the drug smugglers. This project adopts a qualitative research methodology which consists desk based data collection and analysis. In conclusion, it identifies a need for further improvement of our legal system, which may protect the innocent carrier from being punished with severe sentence and to control drug crimes whereby Malaysia is becoming a drug trade's transit.